Valuation of Mangrove Direct Benefit in Jerowaru District, East Lombok Regency, West Nusa Tenggara - Harry Irawan Johari; Sukuryadi Sukuryadi; Ibrahim Ibrahim; Joni Safaat Adiansyah (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Mangroves have various functions and roles, both economic and ecological. In Jerowaru District, East Lombok Regency, the function and role of mangroves are economically and ecologically beneficial, but their value has not been measured. This study aims to determine the valuation of direct benefits of mangroves in Jerowaru District, East Lombok Regency. The approach taken in determining the economic value of mangrove products and services is financial analysis and economic analysis. In financial analysis, a direct approach is used, namely by using market values for marketed commodities and determining the value of substitutes for goods and services that are not marketed. While in the economic analysis, the shadow price or accounting price, namely the value adjusted in such a way as to describe the true value of mangrove goods and services. The results showed that the value of the direct benefit of mangroves in the study area was ± IDR 88.162.750/ha/year. Valuation of the value of direct benefits of mangroves at the location comes from mangrove products and services in the form of firewood and charcoal products, construction wood, capture fisheries products, fish and shrimp larvae stocks, wildlife, preservatives and dyes, food ingredients, and medicines, animal feed, salt, recreation, and tourism, as well as education and research.